Effects of platelet-rich plasma and concentrated growth factor on viability of ultra-diced cartilage grafts in a rabbit model - Kulaksız, Yasin; Yenigün, Alper; Aydın, Mehmet Şerif; Doğan, Remzi; Tuğrul, Selahattin; Özturan, Orhan (My University, 2024)
Background: Although rhinoplastic surgery has progressed considerably in recent years, nasal dorsal irregularities still cause postoperative distress for both surgeons and patients. Purpose: The aim of this study was to measure the association between two biologic graft adjuncts, platelet-rich plasma (PRP) and concentrated growth factor (CGF), and ultra-diced cartilage viability in an animal model. Study Design, Setting, and Sample: This study was designed as a randomized in-vivo study using a rabbit model. Fourteen rabbits were utilized in this investigation. The ultra-diced cartilage was obtained from auricular cartilage. Predictor Variable: The graft biologic adjunct is the predictor variable. There were three treatment groups: graft mixed with PRP or CGF or untreated (control). The grafts were placed in three separate pockets opened on the same rabbit. Grafts were harvested 3 months after insertion for analysis. Main Outcome Variable(s): The primary outcome variable was histopathological and regenerative scores obtained from multiple histopathological parameters indicating the viability of the cartilage. Histopathological score parameters were chondrocyte loss, inflammation, fibrosis, cartilage fragmentation, and calcified area formations in the lacunae. Regenerative score parameters were peripheral cell proliferation in the cartilage tissue, vascularization in the connective tissue, proteoglycan increase in the matrix, and the amount of connective tissue. Covariates: The variables were age, sex, and weight. Analyses: Statistical analysis employed the analysis of variance test, with a significance level of P <.05. Results: The sample was composed of 14 rabbits and 42 samples. The histopathologic scores were 11.93 (±2.49), 8.78 (±2.19), and 6.85 (±1.46) for the control, PRP, and CGF groups, respectively. A statistically significant difference was found in the PRP (P <.0275) and CGF (P <.0001) groups compared to the control group. The regenerative scores were 6.21 (±0.97), 8.85 (±1.70), and 12.07 (±1.26) for the control, PRP and CGF groups, respectively. A statistically significant difference was found in the PRP (P <.0159) and CGF (P <.0001) groups compared to the control group. Conclusion and Relevance: This is the first study investigating the ultra-diced cartilage graft in an experimental animal model. Histopathological examination has shown that mixing ultra-diced cartilage with CGF or PRP increases viability by reducing the histopathological score and increasing the regenerative score.
Keywords: Intercellular Signaling Peptides and Proteins; Platelet-Rich Plasma; Rabbits; Rhinoplasty; Random Allocation; Ear Cartilage; Graft Survival